Combined endoscopic ultrasound‐guided hepaticoduodenostomy with percutaneous reverse rendezvous technique for the treatment of isolate right intrahepatic bile duct stricture. Issue 7 (17th August 2021) - Chantarojanasiri, Tanyaporn; Ratanachu‐ek, Thawee
Abstract : Watch a video of this article.